Observational study of endoluminal mural thrombotic apposition in popliteal artery aneurysm stenting and its relationship with stent-graft geometrical features - Spinella, Giovanni; Conti, Michele; Magliocco, Marco; Pisa, Fabio Riccardo; Finotello, Alice; Pulze, Martina; Pratesi, Giovanni; Cittadini, Giuseppe; Salsano, Giancarlo; Pane, Bianca (Frontiers in Cardiovascular Medicine, 2023)
Introduction The development of intrastent thrombosis is one of the mechanisms related to medium- to long-term failure of endovascular treatment of popliteal artery aneurysm. The present study aims to investigate possible links between the development of endoluminal mural thrombotic apposition in the stented zone (EMTS) with both geometrical features of stent-graft(s) and time of follow-up. Methods Patients with popliteal artery aneurysm who underwent endovascular treatment were recruited during the follow-up period. Segmentation of computed tomography angiography scan was performed to detect femoropopliteal artery lumen, leg bones, EMTS, and stent-graft(s). The following parameters were assessed: number, diameter, and length of stent-graft(s); and shape, volume, and length of thrombotic apposition within the stent(s). The spiral shape of the thrombotic apposition was evaluated as well. Results Eighteen male patients were recruited in the study. EMTS was observed in 13 of them (72%) during the follow-up analysis. An average of 1.8 ± 0.79 stents-grafts were implanted per patient with a median diameter and length of 6.2 (1.9) mm and 125 (50) mm, respectively. The percentage of the stent length where EMTS was present was 42.1 on average (interquartile range: 42.4%) with a mean volume of 206.8 mm3. A positive correlation was found between the length and volume of EMTS (R-squared = 0.71, p < 0.01). Moreover, EMTS had a helical shape in 8/13 patients, with 4/5 with counterclockwise rotation with stent-grafts in the left leg and 3/3 with clockwise direction treated in the right leg. A higher frequency of EMTS was observed in patients with longer follow-up and higher risk factors, as well. Conclusions EMTS is observed in most of the patients under analysis, especially in those with medium- to long-term follow-up. The pattern of such EMTS follows a helical shape having a direction that depends on which leg, right or left, is treated. Our results suggest a close surveillance of popliteal aneurysm stenting by follow-up examinations to control the onset and progression of EMTS.